Modern Technologies For Sustainable Agriculture
01. Application of Biotechnology in Hi-Tech Agriculture Atul Kumar and Vandana A Kumar Chapter 02. Crop Selection an Efficient Tool for Sustainable Agricultural Production in the Impending Climate Change Situation Anil Kumar Singh, UR Sangle and Pravesh Kumar Chapter 03. Management of Soil Fertility for Sustainable Vegetable Production Sobaran Singh, SK Maurya and Poonam Gangola Chapter 04. Microbial Inoculation Through Endophytic Bacteria for Sustainable Agriculture K Swarnalakshmi, M Senthikumar and Sanjay Sachan Chapter 05. Seed Enhancement Technologies for Assured Plant Stand Establishment SK Yadav, Arun Kumar MB, Sangita Yadav, SR Jacob, VA Tonapi and Priya Ranjan Kumar Chapter 06. Technology of Nursery Raising in Vegetable Crops M D Ojha and P K Singh Chapter 07. Pests and Diseases Management of Mango Sandhya Bahuguna, Abhishek Bahuguna and Birendra Prasad Chapter 08. Horti-Silvi-Pastoral System for Development of Watersheds O P Maurya and S Kumar Chapter 09. Biofertilizers and Green Manuring for Sustainable Agriculture Surender Singh, R J Singh, Kuldeep Kumar, Balkar Singh and Livleen Shukla Chapter 10. Plant Growth-Promoting Rhizobacteria for Sustainable Agriculture Ajay Veer Singh and Shachi Shah Chapter 11. Potential of Bio Control, Soil Solarization and Botanicals in Plant Disease Management under Organic Farming. Jameel Akhtar, Zakaullah Khan, Amit Kumar, Dinhesh Chand, Atul Kumar and H.C. Lal. Chapter 12. Mites and their Management Surendra Prasad, Reena and B.K. Sinha Chapter 13. Sustainable Management of Agrobiodiversity Need of the hour Shachi Shah, V Venkat Ramanan, Ajay Veer Singh and Birendra Prasad Chapter 14. Medicinal and Aromatic Plants B Singh, Satender Khari and Aakansha Goswami Chapter 15. Post Harvest Management Technology of Under Utilized Fruits of Arid Zone Shobhana Gupta and RN Prasad Chapter 16. Biotechnological Tools in Modern Agriculture Sangita Bansal and Manisha Mangal Chapter 17. Seabuckthorn : A Miracle Therapeutic Plant of Himalaya Rajander S Bali, H S Chauhan, VK Sah, Abhishek Bahuguna and Birendra Prasad Chapter 18. Implications of Development Communication in the Functioning of KVKS : Key to Sustainable Development Netrapal Malik Ajay Kumar Prabhakar and Ajay Kumar Chapter 19. Lab Animal Care and Their use as Research Animal Models Manish Kumar, Teena Rani and Sunil Kumar Chapter 20. Organic Livestock Production Lokesh Gupta, SP Tailor and Nikhil Gupta Chapter 21. Role of Self Help Group in Poverty Elimination Through Micro Finance Ramesh Singh, OP Maurya, VK Varshney and SS Gangwar